Efektivitas Metode Tim dalam Pelayanan Asuhan Keperawatan di Ruang Perawatan Rsud Otanaha Kota Gorontalo - Sabirin B. Syukur; Arifandi Pelealu; Perci Tamani (Jurnal Ventilator, 2023)
The Care service is an itegral part of the health service included basic service and refered service. The care service done by paramedics are in the forms of care parented . Most petients complain that the medical personels often show unfriendly attitude and lack of interest on the patient needs with simple and careless services . some studies showed that around 33.58% of patient satiasfication was influenced by their perception on service quality . the objective of the research is to know the short time effectivity of them method on care service in Myria hospital.. It is a quantitative descriptive research. The research population were all of 46 paramedics in task the stayed care room. The research sample was the total population , as much as 43 paramedics. The research variables were the effectivity components, onsisting , of productivity, efficiency, and satisfaction. Data were analyzed by the univariat anaiysis on the three variables. The results of research showed that the good respondent productivity were done by 24 personels (44.2%), and poorrespondents productivity were done by 19 personels (55.8%). On the efficiency,variable 23 respondents (53.5%) showed poor efficiency and 20 respondents (46.5%) showed good efficiency ,and on the satisfaction variable , 15 respondent (34.9%) showed high satisfaction and 28 respondents (65.1%) showed low satisfaction. Based on the research result, it is recomended to the Myria Hospital to make some efforts in increasing working productivity by giving a chance to its paramedics to follow some training and higher education programs.